Loss of mothers against decapentaplegic homolog 4 (SMAD4) expression and its correlation with clinicopathological parameters in pancreatic carcinoma - Vareda, Catarina (2021)
Abstract: Pancreatic cancer (PC) has an important role in the clinical and research area representing one of the lowest five-year rates as well as a global mortality rate of 4.8% due to its late and poor diagnosis. Therapeutic strategies have also an unsatisfactory response. Even after surgery, the recurrence or appearance of metastasis are frequent, leading to a poor overall survival. The PC has been related with several mutations, including K-RAS; P16; TP53; HER2. Besides, it is also associated with the deleted in pancreatic cancer locus 4 (DPC4), also known as the suppressor mothers against decapentaplegic homolog 4 (SMAD4) which is present in nearly 50% of the diagnosed patients with PC. Preceding studies proved that SMAD4 loss expression plays an important role in tumorigenesis and in the promotion of pancreatic carcinoma´s growth. Therefore, it is highly relevant in late stages suggesting that SMAD4 may be a molecular biomarker in prognostic results. The main goal of this review is to highlight the foregoing findings focused on SMAD4 deletion and its influence in clinicopathological parameters in pancreatic carcinoma by referring some of the investigations and clinical trials made in this field. Furthermore, it is also required to contemplate some of the therapeutical strategies and the influence of SMAD4 in future therapies